Bias and Discrimination Against Lesbian, Gay, Bisexual, Transgender, and Queer Parents Accessing Care for Their Children: A Literature Review. (April 2023) - Coulter-Thompson, Emilee I.
Background: The experiences of lesbian, gay, bisexual, transgender, and queer (LGBTQ) parents of children with developmental disabilities (DDs) in health and early learning systems are largely understudied. Inclusive, affirming services are critical to timely identification and intervention for DDs. This literature review aimed to establish whether LGBTQ parents experience structural bias and discrimination when accessing care for their children in health and early learning systems. Methods: PubMed, ERIC, and Scopus were searched for empirical research from 1990 to 2020 on: LGBTQ; parents, children, families; bias, disparities, discrimination; and health and early learning services. Themes were analyzed by conceptual model bias levels, participant type, and setting. Results: The search yielded 1, 872 unduplicated records (three through hand search). Twenty-nine articles representing 26 studies in health and early learning in eight countries met the inclusion criteria. Biases common across sectors included challenges surrounding LGBTQ status disclosures; lack of acknowledgment of non-biological parents; and heterosexist forms. Knowledge gaps and negative attitudes about LGBTQ families were found among some professionals and students. Conclusion: Some LGBTQ parents experienced bias and discrimination while accessing care for their children in health and early learning systems. Policies and programs to implement and monitor LGBTQ-inclusive health education and evaluate practice changes are recommended to improve professionals' knowledge, attitudes, and behavior. Multilevel workforce development (e.g., accreditation standards, organizational audits, and training) is needed to create and sustain LGBTQ-affirming health and education environments. Honoring LGBTQ family diversity and reducing health and early learning inequities are critical for improving children's health and education outcomes.